2016
DOI: 10.4028/www.scientific.net/msf.844.19
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric and Chronopotentiometric Study of Nonstationary Processes at the Oxygen-Evolving Anodes in KF–NaF–AlF<sub>3</sub>–Al<sub>2</sub>O<sub>3</sub> Melt

Abstract: Abstract. Some features of behavior and kinetic of the anodic processes for the platinum and Cu–Fe–Ni alloy in the KF–NaF–AlF3–Al2O3 melts at 1025–1055 K have been studied by cyclic voltammetry and chronopotentiometry.The obtained results allowed us to conclude that mechanisms of the anodic processes at the platinum and Cu–Fe–Ni alloy are similar. Both mechanisms include the oxidation stage of electrode material. A rate of this stage is determined to depend significantly on the melt temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The values of sum overvoltages at the current densities, ranging from 0.5 to 1.0 A cm −2 , were 0.4-0.5 and 0.2-0.3 V, respectively. This difference can be explained by a 32,39 and gas bubbles radius.…”
Section: Resultsmentioning
confidence: 97%
“…The values of sum overvoltages at the current densities, ranging from 0.5 to 1.0 A cm −2 , were 0.4-0.5 and 0.2-0.3 V, respectively. This difference can be explained by a 32,39 and gas bubbles radius.…”
Section: Resultsmentioning
confidence: 97%
“…The anodic processes on glassy carbon and platinum, as well as degradation processes on oxygen-evolving anodes in low-melting NaF-AlF3-Al2O3 and KF-AlF3-Al2O3 systems are discussed in [2][3][4][5][34][35][36][37][38]. On the basis of resource tests, it was shown that lowering the temperature to 750-800 °C favourably affects the corrosion resistance of oxygen-evolving anodes, and the study of the anodic process on them seems relevant.…”
Section: Anodic Processmentioning
confidence: 99%
“…The experiments and theoretical modelling of the process on platinum anodes during the electrolysis of the KF-AlF3-Al2O3 melts are presented in [35,36]. Fig.…”
Section: Anodic Processmentioning
confidence: 99%
See 2 more Smart Citations